Non-Sexist Language in CORGA: Description of the Variants Used and Further Reflection - Caíña Hurtado, María; Domínguez Noya, Eva María; López Martínez, María Sol (Madrygal. Revista de Estudios Gallegos, 2019)
Masculine markers have been traditionally used to refer to males and females collectively. However, over the past few decades a growing sector of the population has been claiming that masculine markers cannot be regarded as neutral, given that these do not include gender identities other than masculine. As this use is thought to stem from the male privileges in androcentric societies, the struggle for gender equality has also reached language. Examples show that feminine markers are being made visible while gender binarism is being disfavoured. In fact, several options are being employed, for instance, writing gendered nouns in their masculine and feminine endings (os alumnos e as alumnas, as alumnas e os alumnos), choosing a gender-neutral term (o alumnado) and developing innovative spellings (os/as alumnos/as, as/os alumnas/os, @s alumn@s, xs alumnxs and, more recently, es alumnes). This article focuses on the use of the aforementioned variants in present-day written Galician by analysing the data compiled in the Corpus de Referencia do Galego Actual (CORGA), with a view to launching a linguistic debate on the adoption of a new value for the gender grammatical category and its potential treatment in descriptive grammars.
Keywords: Non-Sexist Language; Corpus; Galician; Grammatical Gender